A systematic review of antimicrobial resistance in Neisseria gonorrhoeae and Mycoplasma genitalium in sub-Saharan Africa. (17th May 2022) - Iwuji, Collins; Pillay, Diantha; Shamu, Patience; Murire, Mercy; Nzenze, Susan; Cox, Laura Ashleigh; Mullick, Saiqa
Abstract: Objectives: Limited antimicrobial resistance (AMR) surveillance coupled with syndromic management of sexually transmitted infections (STIs) in sub-Saharan Africa (SSA) could be contributing to an increase in AMR in the region. This systematic review aimed to synthesize data on the prevalence of AMR in common STIs in SSA and identify some research gaps that exist. Methods: We searched three electronic databases for studies published between 1 January 2000 and 26 May 2020. We screened the titles and abstracts for studies that potentially contained data on AMR in SSA. Then we reviewed the full text of these studies to identify articles that reported data on the prevalence of AMR in Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis and Mycoplasma genitalium in SSA. We summarized the data using a narrative synthesis. Results: The 40 included studies reported on AMR data from 7961 N. gonorrhoeae isolates from 15 countries in SSA and 350 M. genitalium specimens from South Africa. All four SSA regions reported very high rates of ciprofloxacin, tetracycline and penicillin resistance in N. gonorrhoeae . Resistance to cefixime or ceftriaxone was observed in all regions except West Africa. Azithromycin resistance, recommended as part of dual therapy with an extended-spectrum cephalosporin for gonorrhoea, was reported in all the regions. Both macrolide and fluoroquinolone-associated resistance were reported in M. genitalium in South Africa. Studies investigating AMR in C. trachomatis and T. vaginalis were not identified. Conclusions: There is a need to strengthen AMR surveillance in SSA for prompt investigation and notification of drug resistance in STIs.